(untitled) (American Journal of Islam and Society, 2016)
Considering that in the 2015 Federal Election, candidates were often talking about Muslims and their relationship to Canada, whether from an empathetic and supportive position or from a negative and racist position, Kazemipur’s book could not be more welcome and timely. While many of us in the Muslim community wish we were not part of a “question” that needed debating and discussing, Kazemipur’s title is, regrettably, very consciously and aptly chosen, for it refers back to the debates in Europe at the turn of the nineteenth century about the “Jewish Question.” The author notes, as others have, that contemporary debates about “illiberal Muslims” with strange customs who cannot and will not “integrate” into Canadian society mirror those about Jews in that era (pp. 7-8), and proposes to study this particular community through a much needed sociological lens. The book is very well-written, accessible, methodologically and theoretically sophisticated, and enormously useful – anyone who wants to talk about the Muslim experience in Canada will find it insightful and indispensable for coming to terms with day-to-day realities of those experiences. Kazemipur rightly points out that this “Muslim” question is not fruitfully approached through the paradigm proposed by Samuel Huntington and likeminded scholars, namely, “culture,” which forms the basis of a “Muslim exceptionalism” (p. 5) and explains the “inability” of Muslims to integrate into western democracies. This approach, he argues, “grossly oversimplifies a Book Reviews 127 complex and multifaceted problem” and “removes the possibility that the mainstream population might have to take some moral responsibility for it” (p. 5). Integration is a relationship among different peoples. Thus he also points out, although not until the end of the book, that trying to understand these Muslims’ situation by focusing upon Islamic theology is less useful than ...